2009
DOI: 10.1016/j.otsr.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Mini-invasive nail versus DHS to fix pertrochanteric fractures: A case-control study

Abstract: This study has shown the benefits of the BCM nail in terms of stability. But the potential advantages of this mini-invasive technique were limited by ancillary-related difficulties which need to be rectified. These preliminary results are in favour of a further development of this innovating device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…The literature comparing blood loss in intertrochanteric hip fractures treated with intramedullary nail or DHS is inconclusive. Authors have reported reduced blood loss, [25][26][27] increased blood loss 28 and no difference 29,30 in patients with intertrochanteric fractures treated with an intramedullary nail. The variability among studies may be related to differences in fracture severity, as patients with more displaced fractures are generally more likely to be treated with an intramedullary device.…”
Section: Discussionmentioning
confidence: 99%
“…The literature comparing blood loss in intertrochanteric hip fractures treated with intramedullary nail or DHS is inconclusive. Authors have reported reduced blood loss, [25][26][27] increased blood loss 28 and no difference 29,30 in patients with intertrochanteric fractures treated with an intramedullary nail. The variability among studies may be related to differences in fracture severity, as patients with more displaced fractures are generally more likely to be treated with an intramedullary device.…”
Section: Discussionmentioning
confidence: 99%
“…Similar percutaneous compressing plate systems have been compared with DHS for treatment of intertrochanteric fracture that showed good stability and healing rates [20]. Meta-analysis by Ma et al [21] also demonstrated the advantages of a similar system with respect to operation time, blood loss and cardiovascular event but not in functional outcome compared with DHS system.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies comparing the outcomes of the PFNA and DHS for peritrochanteric fractures, but there is obvious inconsistency of effects across those studies and the optimal management of peritrochanteric fractures remained controversial [8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thus, to provide the most comprehensive assessment of the PFNA and DHS for peritrochanteric fractures, we performed this meta-analysis by including five randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Established surgical options for peritrochanteric fractures mainly include DHS, Gamma nail, and proximal femoral nail, but the optimal treatment choice continues to be highly debated [30,31,[33][34][35][36]. The PFNA is an intramedullary device with a helical blade rather than a screw for better purchase in the femoral head and has been adopted for patients with unstable peritrochanteric fractures [5][6][7].…”
Section: Discussionmentioning
confidence: 99%